(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper presents a numerical study on the behavior of a longline system with lantern nets subjected to wave and current loads. The system consists of a main longline secured at both ends by chains connected to anchor points, along with buoys and lantern nets suspended from the longline. The system is modeled using OrcaFlex, employing a lumped-mass approach for line objects. Hydrodynamic loads are incorporated through an extended form of the Morison equation, with drag and inertia coefficients sourced from the literature. The study examines the system’s response under various environmental conditions, including different wave heights, periods, current speeds, and headings. Regular waves are analyzed in combination with currents. The operating depth of the lanterns is explored as a potential adjustable parameter that could be optimized for both productivity and survivability. This study investigates how variations in depth affect system performance, as lowering the lanterns may help reduce wave-induced loads and motions. To accommodate different lantern depths, five design variations are proposed and evaluated. Anchor loads and lantern motions are analyzed and compared, using the baseline model as a reference. All design variations were evaluated based on multiple performance criteria. DV1 and DV2 reduced horizontal lantern motion and mean inclination due to deeper lantern placement, with DV2 also decreasing anchor loads by using longer buoy lines. DV3, which incorporated fewer surface buoys and a submerged longline, achieved a significant reduction in anchor tension, up to 40% compared to the baseline, while also minimizing lantern motion and maintaining compatibility with existing infrastructure. DV4, which used ballasted lanterns, effectively reduced mean inclination by up to 74%, but increased anchor loads due to the added weight. DV5 performed similarly to DV4, notably reducing mean inclination and increasing anchor loads, but also introduced operational complexity due to its double longline configuration.